Transesophageal electrocardiography before and after intervention in atrio-ventricular nodal reentrant tachycardia - A. V. Tarasov; K. V. Davtyan; R. M. Beniya; Yu. M. Pozdnyakov (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study diagnostic value of transoesophageal electrocardiography (TE ECG) in verifying double physiology of atrio-ventricular (AV) node in differential diagnostics of supraventricular tachycardias (SVT), as well as in assessment of short and long-term treatment results in paroxysmal AV nodal reentrant tachycardia (PAVNRT).Material and methods. The study included 32 patients with PAVNRT diagnosis, verified by TE ECG. At Stage I, PAVNRT patients were clinically examined. Then intracardiac (IC) ECG and radioablation (RA) were performed at a Cardiosurgery department. At Stage II, all participants underwent TE ECG, to assess RA effectiveness 1 and 3 months later.Results. At Stage I, TE ECG demonstrated some specific features of AV node physiology. Their impact on treatment effectiveness and post-intervention clinical course was assessed at Stage II. PAVNRT in combination with impaired AV conductivity and increased effective refractory periods (EFP) of beta-pathway (>500 ms) were not contraindicative to RA of slow AV node pathways. Among these patients, AV conductivity was satisfactory, with no clinical symptoms or signs. During TE ECG, PAVNRT was difficult to diagnose in patients without double AV node conductivity and wide QRS tachycardia.Conclusion. The results obtained confirmed the importance of ТЕ ECG in PAVNRT diagnostics. RA is needed in patients with confirmed diagnosis and double AV node physiology. This method is important for identifying indications and counter-indications for intervention, for predicting complications and adverse events during RA.